2019
DOI: 10.3390/sym11040461
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral Regional Growth and Convergence in Ecuador: An Analysis of the Intra-Distributive Dynamics of Productivity

Abstract: The objective of this research is to examine growth and convergence processes in the provinces of Ecuador, considering sectoral productivity as an analysis variable. To do so, evidence of the productivity of the agricultural, secondary and service sectors is presented, and by applying the non-parametric method of density functions of the kernel, the complete distribution of the data is analyzed. The results obtained indicate that territorial inequality in Ecuador has very different behavior depending on the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
8
0
2
Order By: Relevance
“…The results also demonstrate, however, that convergence is conditional on the period being examined. Regressions testing for Ecuadorian economic convergence over shorter subperiods of the complete 1992–2013 period under study find that most of the convergence behavior took place over the 1992–2002 period (which is consistent with Quintana‐Romero et al, 2019), with no statistically significant convergence tendency identified in the data over the 2002–2013 period. This is unexpected as the convergent period was also one of the economic and political tumult and limited resources of central government bodies to support such a transition.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The results also demonstrate, however, that convergence is conditional on the period being examined. Regressions testing for Ecuadorian economic convergence over shorter subperiods of the complete 1992–2013 period under study find that most of the convergence behavior took place over the 1992–2002 period (which is consistent with Quintana‐Romero et al, 2019), with no statistically significant convergence tendency identified in the data over the 2002–2013 period. This is unexpected as the convergent period was also one of the economic and political tumult and limited resources of central government bodies to support such a transition.…”
Section: Resultssupporting
confidence: 78%
“…What is found in this study is that Ecuador has experienced a process of provincial economic divergence once spatial contiguity in the econometric estimation is considered. Finally, Quintana‐Romero, Correa‐Quezada, Ramón‐Mendieta, and Álvarez‐García (2019) investigate provincial convergence over the period 1993–2007 4 and indicate that there exists both β‐ and σ‐convergence over this period 5 . A complete study of the 1992–2013 period using consistent and reliable income data has yet to be undertaken.…”
Section: Convergence Concepts and Their Applications To Within‐countrmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the variables of 21 of the 24 Ecuadorian Provinces are taken into account. Galápagos was not considered because it is an insular region outside the continent, which does not allow for involving it in the spatial methods (neighborhood effect and contiguity) used in this study, as Quintana et al [96] points out. However, in the data of the provinces of Santo Domingo and Santa Elena, Pichincha, and Guayas were incorporated, respectively, since they are of recent creation (year 2009, before this year they were administratively part of Pichincha and Guayas), so it is not possible to have provincial accounts for previous years.…”
Section: Study Variablesmentioning
confidence: 99%
“…This clustering effect of human activities overburdens the natural and social progressions, brings significant mutation to the socioeconomic dimension, and causes an increasingly polarized and spatial restructure in the urban system. Every so often, this process triggers unequal gentrification and segregation in communities and income groups, especially in the distribution of urban services, civic spaces, public health, and other essential amenities (Duggal 2020 ; Ling et al 2020 ; Sharifi and Khavarian-Garmsir 2020 ; Ilgen et al 2019 ; Quintana-Romero et al 2019 ; Krefis et al 2018 ; Ling and Lin 2018 ; Lechner et al 2016 ; Vale 2014 ).…”
Section: Introductionmentioning
confidence: 99%